Structural injustice, marginality, and neurolaw: a normative comparative and theoretical approach - Díaz-Soto, José Manuel; Borbón, Diego (Frontiers in Sociology, 2024)
In this paper, we introduce a perspective based on a comparative viewpoint on the Colombian Penal Code and a theoretical approach to neurolaw and criminal responsibility in contexts of marginality and extreme poverty. We present a further response to the debate on how structural injustice impacts criminal responsibility. By offering a comparative and theoretical insight, this paper enriches the debate and provides an understanding of how legal systems might address these issues. The paper then suggests that other legislations can follow the rule of Article 56 of the Colombian Penal Code, which reduces punishment in circumstances of marginality, ignorance, or extreme poverty. Utilizing neuroscience findings, we briefly highlight the interplay between structural injustice and neurobiological vulnerabilities, emphasizing the complexity of the role of incarceration and criminal law in marginalized populations. We invite scholars to consider debates on alternatives to criminal law, the reduction of prison use and mass incarceration, as well as further remarks on the problem of free will. In this paper, we seek to bridge the gap between neuroscientific insights and socio-legal ethics to foster a more equitable and humane system of justice.